2021
DOI: 10.1016/j.heliyon.2021.e08523
|View full text |Cite
|
Sign up to set email alerts
|

3-O-Acetyl-11-keto-β-boswellic acid ameliorates acquired, consolidated and recognitive memory deficits through the regulation of hippocampal PPAR γ, MMP9 and MMP2 genes in dementia model

Abstract: Pentacyclic Phytomolecule 3-O-Acetyl-11-keto-β-boswellic acid (AKBA) from Frankincense family has proven for the neuroprotection and recognized as an orphan drug for the treatment of cerebral edema. Nonetheless, AKBA have promising indications with Peroxisome proliferator activated receptor gamma (PPARγ) associated to cognitive function not deliberated so far. In order to substantiate the potential role of AKBA on memory function, we examine the contribution of PPARγ activation and its downstream process. Modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Another study indicated that a possible mechanism for the beneficial effects of BAs may include inhibition of the 5-LOX/COX pathway in arachidonic acid metabolism, activation of Nrf2 (has anti-inflammatory activity), through binding to ARE (antioxidant response element) and inhibition of NF-kB (Siddiqui et al 2021 ). Furthermore, BAs eliminate memory impairment by enhancing the activity of PPARγ and its downstream regulators, matrix metalloproteinase 2 genes in the hippocampus (Gunasekaran et al 2021 ). In a double-blind, randomized, placebo-controlled clinical trial, the effect of BAs on cognitive impairment after traumatic brain injury (TBI) was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Another study indicated that a possible mechanism for the beneficial effects of BAs may include inhibition of the 5-LOX/COX pathway in arachidonic acid metabolism, activation of Nrf2 (has anti-inflammatory activity), through binding to ARE (antioxidant response element) and inhibition of NF-kB (Siddiqui et al 2021 ). Furthermore, BAs eliminate memory impairment by enhancing the activity of PPARγ and its downstream regulators, matrix metalloproteinase 2 genes in the hippocampus (Gunasekaran et al 2021 ). In a double-blind, randomized, placebo-controlled clinical trial, the effect of BAs on cognitive impairment after traumatic brain injury (TBI) was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…An amnesic rat model was created by the administration of scopolamine (2 mg/kg in saline; IP). Duration and dose of scopolamine injection were determined according to recent investigations [ 19 , 22 , 21 ]. The treatment groups (groups 3–6) received 10, 15, 20, or 30 mg/kg of minocycline, whereas the scopolamine group and group 1 received the vehicle for two weeks [ 23 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Evidence suggests multiple neuroprotective mechanisms of minocycline in different pathological conditions [ 12 ]. Noticeably, scopolamine attenuates the activity of the cholinergic system in the brain tissue [ 19 , 20 ]. Hence, in the present study, we investigated whether treatment with minocycline can reverse scopolamine-mediated memory deficits via AChE and oxidative stress markers in the brain.…”
Section: Introductionmentioning
confidence: 99%